Expressive Writing Therapy in Group Counseling to Reduce Academic Anxiety in Students at Al Huda Senior High School, Pekanbaru - Elsa Maheswari; Riswani Riswani (AMK : Abdi Masyarakat UIKA, 2026)
This research was instigated with the high levels of academic anxiety experienced by students at school impacting their concentration, decision-making skills, and academic achievement. This research aimed at describing the levels of student academic anxiety before and after the implementation of Expressive Writing Therapy technique in group counseling and determining the effectiveness of Expressive Writing Therapy technique in group counseling to reduce student academic anxiety. Quantitative approach was used in this research with quasi experimental method with a research design, namely one group pretest posttest. Purposive sampling technique was used. The samples consisted of 5 eleventh-grade students at Senior High School of Al Huda Pekanbaru, who had high levels of academic anxiety. The instrument used was academic anxiety questionnaire with Likert scale. The research findings showed that student academic anxiety levels before the treatment were in high category, and they were in moderate and low categories after the implementation of Expressive Writing Therapy technique in group counseling. The research findings showed that Expressive Writing Therapy technique in group counseling was effective in reducing student academic anxiety at Senior High School of Al Huda Pekanbaru. Based on Wilcoxon Signed Rank Test result, the score of Z was -2.032b, and Asymp. Sig. (2-tailed) was 0.042 lower than 5% (0.05) significant level. Therefore, Null hypothesis (H0) was rejected, and Alternative hypothesis (Ha) was accepted.